Analysis of Packaging Machine Effectiveness with Overall Equipment Effectiveness and Six Big Losses : Analisis Efektivitas Mesin Packaging Menggunakan Metode Overall Equipment Effectiveness dan Six Big Losses - Acyuta Intan Nurardisa; Yekti Condro Winursito (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This study was conducted at PT XYZ, which is the largest food and beverage manufacturing industry in Indonesia. This company has several machines in the production process, one of which is a packaging machine. This machine is very susceptible to damage, because it is often used in the production process. This study aims to analyze the effectiveness of packaging machines by applying the Overall Equipment Effectiveness (OEE) and Six Big Losses methods. OEE is applied to measure machine performance based on three main aspects, namely availability, performance and quality, while Six Big Losses are used to determine the main factors of efficiency loss. Data were collected through direct observation and production data. The results of the study found that the OEE value of the packaging machine was still below standard with a value of 74.21%, and reduce speed losses of 12.78% as the main cause of efficiency loss. Based on these findings, improvements in machine maintenance, operator training, and improvements to product standards are recommended, in order to increase machine effectiveness.